Study on dysphagia from 2012 to 2021: A bibliometric analysis via CiteSpace - Sun, Weiming; Kang, Xizhen; Zhao, Na; Dong, Xiangli; Li, Shilin; Zhang, Gaoning; Liu, Guanxiu; Yang, Yang; Zheng, Chafeng; Yu, Guohua; Shuai, Lang; Feng, Zhen (Frontiers in Neurology, 2022)
Objectives: To review the document related to dysphagia, summarize the research direction, analyze the research hot spots and frontiers, report the research trends and provide new ideas for future development in the field via CiteSpace. Methods: This study retrieved articles related to dysphagia from 2012 to 2021 from Web of Science Core Collection database. Downloading all datas and then utilized CiteSpace V.5.8.R3 (64-bit) to analyze the number of publications annually, cited journals, countries, institutions, authors, cited authors, cited references and keywords respectively. Visualized the data with a knowledge map, collaborative network analysis, cluster analysis, and strongest citation burst analysis. Results: A total of 14007 papers were obtained with a continually increased trend over time.The most productive country and institute in this field were The United States (4308) and Northwestern University (236), respectively. Dysphagia (5062) and Laryngoscope (2812) was the most productive journal. Elizabeth Wardhad the highest number of publications (84). Logeman JA’s te al article (centrality:0.02) was the most symbolic references. The most common keywords were dysphagia, management, quality of life, deglutition disorder, diagnosis, aspiration, prevalence, children, outcome and oropharyngeal dysphagia. Conclusion: This study analyzed the current situation of dysphagia field via CiteSpace, then identify the research hot spots and frontiers on dysphagia. Current global trends in dysphagia researches and the growing public awareness of health care and quality of life suggest that dysphagia researches will grow in popularity with further breakthroughs.